Separation, extraction and concentration processes in the food, beverage and nutraceutical industries - Rizvi, S. S. H., 1948- (Woodhead Pub., 2010)
Separation, extraction and concentration are essential processes in the preparation of key food ingredients. They play a vital role in the quality optimization of common foods and beverages and there is also increasing interest in their use for the production of high-value compounds, such as bioactive peptides from milk and whey, and the recovery of co-products from food processing wastes. Part one describes the latest advances in separation, extraction and concentration techniques, including supercritical fluid extraction, process chromatography and membrane technologies. It also reviews emerging techniques of particular interest, such as pervaporation and pressurised liquid extraction. Part two then focuses on advances in separation technologies and their applications in various sectors of the food, beverage and nutraceutical industries. Areas covered include dairy and egg processing, oilseed extraction, and brewing. This section discusses the characteristics of different foods and fluids, how food constituents are affected by separation processes and how separation processes can be designed and operated to optimize end product quality. With its team of experienced international contributors, Separation, extraction and concentration processes in the food, beverage and nutraceutical industries is an important reference source for professionals concerned with the development and optimisation of these processes. Describes the latest advances in separation, extraction and concentration techniques and their applications in various sectors of the food, beverage and nutraceutical industriesReviews emerging techniques of particular interest, such as pervaporation and pressurised liquid extractionExplores the characteristics of different foods and fluids and how food constituents are affected by separation processes.
Keywords: Food industry and trade -- Technological innovations.; elektronické knihy; electronic books